Grande dicionário da língua portuguesa - António de Morais Silva (Confluência)
1.º vol.: A - Armadas, 1114 p.; 2.º vol.: Arma de Cestina, 1114 p.; 3.º vol.: Cesto - Desvalor, 1114 p.; 4.º vol.: Desvalora - Eza, 1051 p.; 5.º vol.: Iridiar, 1045 p.; 6.º vol.: Irídico - Moreáceo, 955 p.; 7.º vol.: Moreão - Pebrina, 955 p.; 8.º vol.: Peça - P. V., 897 p.; 9.º vol.: Q - Seival, 1003 p.; 10.º vol.: Seive - Tomar, 955 p.; 11.º vol.: Tomara - Zuzara, 905 p.; 12.º vol.: Adenda - Vocabulário, 1098 p.